DETERMINAN KEPUTUSAN PEMBELIAN PRODUK: SATU PENDEKATAN KONSEP CRM - Andriyanto, Dicky; Ardhitya Alam Wiguna; Mayasari, Financia; Aditya Nizar Al Ardi; Resya, Fachmi; Yuniar, Eka (Bisma: Jurnal Bisnis dan Manajemen, 2025)
Business development requires every business actor to increase profits and sustainability as part of economic productivity. Purchasing decisions as a stimulus in achieving profit and business sustainability can be achieved with strategic innovation in the aspects of product, price, location, and promotion. This study aims to determine and analyze the effect of marketing mix on coffee purchasing decisions at Tempo Doeloe shop. This research uses a survey method. The type of data used is primary data sourced from questionnaires filled out by respondents. The data analysis technique used is multiple linear regression analysis using IBM SPSS Statistics 22. The results showed that the price factor played an important role in influencing consumer decisions to buy products, while product, location, and promotion factors had no significant effect.